SciVee 2008
DOI: 10.4016/6135.15
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the DOTS Framework for Tuberculosis Control to the Management of Non-Communicable Diseases in Sub-Saharan Africa

Abstract: Adapting the DOTS framework for tuberculosis control to the management of non-communicable diseases in sub-Saharan Africa. PLoS Med 5(6): e124.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Given the sequelae that can ensue after fi stula repair, we would emphasise the importance of implementing a system of cohort monitoring of all patients who undergo obstetric surgery for fi stula. 18,19 Other chronic diseases such as tuberculosis and human immunodefi ciency virus/acquired immunedefi ciency syndrome also require long follow-up periods, and cohort monitoring is routinely used to judge programme success. Quarterly cohort reporting is also advantageous, as it would provide useful operational information on all newly operated cases (disease burden) and their standardised outcomes (such as closed fi stula, continence, loss to follow-up, death or transferred out).…”
Section: Discussionmentioning
confidence: 99%
“…Given the sequelae that can ensue after fi stula repair, we would emphasise the importance of implementing a system of cohort monitoring of all patients who undergo obstetric surgery for fi stula. 18,19 Other chronic diseases such as tuberculosis and human immunodefi ciency virus/acquired immunedefi ciency syndrome also require long follow-up periods, and cohort monitoring is routinely used to judge programme success. Quarterly cohort reporting is also advantageous, as it would provide useful operational information on all newly operated cases (disease burden) and their standardised outcomes (such as closed fi stula, continence, loss to follow-up, death or transferred out).…”
Section: Discussionmentioning
confidence: 99%
“…5 In a previous publication, we have described how the DOTS paradigm could be adapted for the management of non-communicable diseases, focusing on political commitment, case finding, standardised treatment, standardised monitoring, evaluation and drug quantification. 6 We have also explained how this model could be implemented and scaled up in a phased approach at the country level. Since then, we have further developed our thoughts on the monitoring component of this model.…”
Section: Vital Signs Of Chronic Disease Managementmentioning
confidence: 99%
“…The treatment card and the register are the two important tools for monitoring vital signs of chronic diseases, and how these might look and function at the clinic level have already been described. 6 Treatment cards provide the complete chronological follow-up history for each patient, whilst registers provide an up-to-date summary at any moment in time of the current outcome status of all registered patients, provided of course that data in treatment cards are regularly updated to the registers.…”
Section: Recording and Reporting On Vital Signsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a number of authors have suggested that it is possible to adapt HIV programs or MCH programs to address NCDs. [24][25][26][27] It is commonly recognized that health systems in many low-income countries are not oriented to provide the continuity of services that is necessary to effectively identify the NCD patients. 28 Those at risk for developing NCDs need systems already in place that can help them participate in their care, and most importantly to get them to recognize that appropriate care requires a lifelong commitment on their behalf.…”
Section: However There Is Still More Research To Be Donementioning
confidence: 99%